Phosphorus Status, Inorganic Phosphorus Forms, and Other Physicochemical Properties of Acid Soils of Farta District, Northwestern Highlands of Ethiopia - Asmare Melese; Heluf Gebrekidan; Markku Yli-Halla; Birru Yitaferu (Applied and Environmental Soil Science)
Soil acidity and low availability of P limit crop production in the highlands of Ethiopia. The objective of this study was to determine the P status, distribution and forms of inorganic P and relate them to selected chemical properties of eight representative acidic surface soil samples from Farta District. Soil pH (H2O) varied between 4.74 and 5.50. The moderate to high CEC suggests that besides kaolinite, the soils also contain expandable 2 : 1 clay minerals. Though the total P content was high, the available Olsen P content was very low or low in all soils except one. In most soils, the abundance of inorganic P fractions was as follows: P bound by oxalate extractable iron (Feox-P) > reductant soluble Fe-P > occluded Al-Fe-P > P bound by oxalate extractable aluminum (Alox-P) > calcium bound P (Ca-P). Olsen P had a very strong positive correlation (P≤0.01) with Alox-P (r=0.98), Feox-P (r=0.96), and oxalate extractable P (r=0.94). Though Fe bound P reserves were quite abundant and the degree of P saturation of Alox + Feox (median 3.3%) was moderate, the extremely low P saturation of Alox (median 0.5%) explains the P deficiency of the soils.